KEMAMPUAN JAMUR TIRAM (Pleurotus ostreatus) SEBAGAI SUPLEMEN UNTUK PENINGKATAN SEKRESI AIR SUSU DAN DIAMETER ALVEOLUS KELENJAR AMBING MENCIT - I.B. Rai Pidada; Listijani Suhargo (The East Java Biological Society, 2007)
This study was aimed to know the effects of oyster mushroom supplement to milk secretion and mammary alveolus diameter of mice. The research was carried out under laboratory condition at the laboratory of Reproduction Biology, Faculty of Mathematic and Sciences, Airlangga University by using Complete Random Method. The study was designed by using totally 32 mice post partum (PP) and devided into four groups of treatment which consisted 8 female mice post partum of each group. The groups are: (a) the control groups, the groups that were given 0.2 ml aquadest, (b) the treatments of oyster mushroom solution with 3 variation of mushroom concentration, there are 2%, 4% and 6%. The oyster mushroom solution was given by gavage. The treatments were started on 3th to 12th day of lactation period. The increasing of milk secretion were showed by the increasing of body weight of offsprings. The data were collected from the difference result of the balance of weight body of offspring and the data were observed on 4th, 6th, 8th, 10th, and 12th of lactation periode and then on 13th day, the mice (five mice for each group) were killed to make histological preparat of mammary glands. The datas were analyzed by ANOVA and LSD test (a = 0.05). The results of this research showed that oyster mushroom supplement can increase milk secretion and mammary alveolus diameter of mice. Oyster mushroom with 6% concentration gave the best effects And there was a positive corelation between the weight of oyster mushroom that was used with the increasing of the oyster mushroom effects.